Decomposing the size, value and momentum premia of the Fama–French–Carhart four-factor model - Rath, Subhrendu; Durand, Robert (Elsevier, 2015)
The size, value and momentum premia in the Fama–French–Carhart four-factor model may be decomposed in terms of observable firm characteristics including leverage.